Alfabetização geográfica: o ensino de geografia nas séries iniciais do ensino fundamental - Marques, Valéria Maria (2009)
This job consist in investigate as literacy in Geography has been board in initial series of the basic teaching, exatle first and second years. The study started of the idea that literacy is so much more than teach someone to read and write or decifre some linguistics codes- we understand the literacy is a process of building/decode the meaning of symbols. This conception allowed us to think about literacy in Geography, in this form, this subject was boarded with a proprer language, with specific symbol struturation and therefore, suscetible to be developed in the literacy process. The investigation had been accompleshed whit twelve teachers who teach in state and municipal schools, and it had interviewee in their cities in Itajobi, Pindorama and Catanduva, countryside of São Paulo. In the first chapter of this job has been accomplish biblyografic study of Geography teach in initial series according thesis and dissertations that has written between 1982 and 2007. The second one, board the question about literacy, literacy in Geography and language. In sequence, in third chapter, we started analyse the difficults aspects leaders, we analysed the teachears conceptions in connection of their formation and their teach practice in connection to Geography teach in initial series in basic teaching. After that, it has been checked the objetctives and contents leaders, to intent understending how and which problems leaders are connected to the topic of discussion